Phylum Gastrotricha. In: Zhang, Z.-Q. (Ed.) Animal Biodiversity: An Outline of Higher-level Classification and Survey of Taxonomic Richness (Addenda 2013) - Balsamo, Maria; Guidi, Loretta; D’hondt, Jean-Loup (Zootaxa, 2013)
An updated classification of the two orders of the phylum is provided up to family level, and numbers of genera and species described so far are specified. The phylum is composed of two orders: Macrodasyida, with, 9 families, 33 genera (+1 genus incertae sedis) and 338 species (+1 species incertae sedis), and Chaetonotida, with 8 families, 30 genera and 454 species. Current taxonomy is relatively stable for the order Macrodasyida, except for the presence of a monotypic genus which cannot yet be assigned with certainty to any of the existing families. On the contrary, the taxonomy of the order Chaetonotida has been repeatedly revised in the last decades and is still unstable. An integrate taxonomical approach on morphological and molecular bases appears necessary in order to revise the current classification according to phylogenetic relationships.